Regional trade and investment value chains in South Asia: Perspectives from Pakistani enterprises (Quest Journal of Management and Social Sciences, 2019)
Background: South Asian countries still maintained barriers to trade including regulatory restrictions on Foreign Direct Investment, non-tariff barriers and lack of banking channels. These restrictions are not only affecting the regional trade integration but also affecting the transfer of skills and technology among the member countries.Objectives: This study examines the factors that are inhibiting the development of regional integration for Pakistan in South Asia.Methods: The study conducted interviews of business community in Karachi and Peshawar regarding regional trade, investment and value chains.Result: The results pointed out that political difference with neighboring countries affect the regional integration in the form of lower trade and investment volume. Engaging in value chains is a way forward to promote trade flows and regional integration which will be beneficial for the trading partners in terms of economic growth and employment.Conclusion: Pakistan contains weak investment outlay in South Asia as currently investment agreements with only Bangladesh and Sri Lanka existed. The reasons for lower FDI inflows in Pakistan include lack of political stability, inadequate infrastructure and non-transparent government regulations.Implications: This study provides tentative picture of regional trade and investment in South Asia and the result generated can be used by concerned authorities, investors of those areas.Recommendations: Simplifications in investment laws, piracy of intellectual property, relaxing current account restriction and single channel for streamlining information regarding support, opportunities, investment and market rules and regulations can enhance the investment volume.